Guishaozichuan granules can attenuate asthma in rats via the MUC5AC/EGFR signaling pathway - Gao, Qinqin; Feng, Chenran; Shi, Qi; Wang, Qingling; Ding, Zitong; Chu, Huilun; Kong, Deming; Yin, Xingbin; Ni, Jian; Sun, Wenyan; Li, Youlin (Frontiers in Pharmacology, 2023)
Background: Guishaozichuan (GSZC) granules are a traditional Chinese medicine formulation created by Professor Li (Chinese–Japanese Friendship Hospital, Beijing, China) We studied the effect of GSZC granules in rats suffering from asthma. Methods: Specific pathogen-free Sprague–Dawley rats were divided randomly into seven groups. Ovalbumin (OVA) and Al(OH)3 gel were used to create an asthma model. On day 1, rats were injected with OVA (10 mg) and an Al(OH)3 gel suspension (100 mg). One week later, rats were sensitized again. On day 15, rats were given aerosolized OVA (1%) for 30 min/day for 10 days. Gastric administration of OVA was 1 h before nebulization. At 24 h after the last stimulation, changes in airway resistance (RI) and dynamic compliance (Cdyn) in rat lungs were measured after challenge with methacholine at increasing concentrations. The contents of immunoglobulin (Ig)E, interleukin (IL)-4, IL-5, IL-13, and IL-17 in serum were measured by enzyme-linked immunosorbent assays. The percentage of eosinophils (EOS) and the white blood cell (WBC) count in bronchoalveolar lavage fluid (BALF) were counted under an optical microscope. Pathologic alterations in lung tissue were evaluated by optical microscopy, and lung injury score calculated. Expression of mucin 5AC, oligomeric mucus/gel-forming (MUC5AC) and epidermal growth factor receptor (EGFR) in lung tissue was measured by immunohistochemistry. mRNA expression of MUC5AC and EGFR in lung tissue was measured by real-time reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Results: GSZC granules reduced RI markedly and improved Cdyn, decreased serum levels of IgE, IL-4, IL-5, IL-13, IL-17, %EOS and the WBC count in BALF. GSZC granules alleviated lung-tissue damage, diminished the Inflammation Score, and reduced mRNA and protein expression of MUC5AC and EGFR in lung tissue. Conclusions: GSZC granules could improve bronchial hyperresponsiveness, bronchial inflammation, and histopathologic damage in the lungs of rats suffering from asthma. This phenomenon may be related to its regulation of cytokine levels and the MUC5AC/EGFR signaling pathway.